Marcel und die Schauspieler: Formen der Rezeption im architektonischen und figürlichen Werk von Isa Genzken - Becker, Sabine (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2017)
The research project focuses on the artistic work of Isa Genzken (born in 1948). A characteristic feature of the artist's work is a formal connection to the artistic practices of minimal art. At the same time, the artist uses forms and motifs that are decipherable through the viewer's individual and collective knowledge. Her sculptures and installations from the last fifteen years in particular exhibit a consistent development from a formalist idiom to a mixed-media installation technique that also employs figurative pictorial elements. The dissertation demonstrates how Isa Genzken offers the viewer various forms of reception by combining a minimalistic reduction in form with semantic potential. These forms of reception focus on the one hand on physical perception, allowing the viewer to experience architectural realities, while on the other hand they invite semantic interpretation. Taking these assumptions as a starting point, the dissertation aims to show what effect this tension between minimalism and semantics has on the viewer's reading and experience of the works. The research project presented in the dissertation transcends individual visual arts disciplines and is located within the context of philosophical and art historical aesthetics. With an approach centered on the theory of aesthetic experience, the dissertation therefore provides the first systematic art historical and historical study of Genzken's early works, and particularly of her most recent works. The study compares these two creative periods in two case studies: Marcel (1987) from her series of concrete sculptures (1985-1991) and Schauspieler II/III (2014/2015).

Gegenstand des Forschungsvorhabens ist das künstlerische Werk von Isa Genzken (geb. 1948). Untersucht werden rezeptionsästhetische Formen des frühen, architektonischen Werkes sowie jüngster, figürlicher Arbeiten. Charakteristisch für das Gesamtwerk der Künstlerin ist ein formaler Bezug zur künstlerischen Praxis der Minimal Art. Zugleich verwendet die Künstlerin Formen und Motive, die über das individuelle und das kollektive Wissen des Betrachters entschlüsselbar sind. Vor allem in den jüngsten Skulpturen und Installationen lässt sich eine konsequente Entwicklung von einer formalistischen Formensprache hin zu einer medienhybriden, installativen Arbeitstechnik unter Verwendung auch figürlicher Bildelemente feststellen. Ziel der Dissertation ist es zu begründen, inwiefern die unterschiedlichen Lesarten, die sich aus diesem Spannungsverhältnis ergeben, der in der Kunsttheorie der Moderne gängigen Unterscheidung von "literaler" und "illusionistischer" Kunst widersprechen, die anlässlich des gesteigerten Literalsinns der Minimal Art aufgestellt wurde.
Marcel and the Actors: Forms of reception in the architectural und figural work of Isa Genzken
Keywords: Rezeption; Architektur; Anthropomorphismus; Ästhetik; Genzken, Isa; 700 Künste; Bildende und angewandte Kunst